Making viruses more socially acceptable - Carradore, Roberto (Teorija in praksa, 2019)
A new class of biopesticides in agriculture is being developed in Europe. This biotechnological innovation is based on the use of a virus as a biocontrol agent and is presented by scientists in response to the EU policy of reducing chemical pesticides; yet, the negative social image of viruses could act as a brake on innovation and worsen the fiduciary pact existing between technoscience and society. This contribution aims to trace the theoretical space for social acceptability within risk analysis, first by looking at how the scientific image of viruses has changed and, second, by proposing a sociological framework for investigating the social image of virus-based biotechnological innovations.
Keywords: Agriculture; analiza tveganja; biopesticidi; Biotechnology; Biotehnologija; družbena sprejemljivost; Kmetijstvo; Pesticides; Pesticidi; Sociologija znanosti; Sociology of science; virusi